SISTEM INFORMASI PENGELOLAAN DONASI BEASISWA DENGAN NOTIFIKASI WHATSAPP BERBASIS WEBSITE PADA SEKOLAH TINGGI ILMU KOMPUTER YOS SUDARSO - Deliyo Rival (Electro Luceat, 2025)
The manual management of scholarship donations at the Yos Sudarso College of Computer Science in Purwokerto presents several challenges, including the risk of recording errors, reporting delays, and a lack of transparency for donors. This research aims to design and build a web-based scholarship donation management information system integrated with WhatsApp notifications to enhance operational efficiency and transparency. The system was developed using the Prototyping method with the Laravel framework and a MySQL database. System functionality was tested using White Box and Black Box Testing methods, while system evaluation employed a Paired Sample t-Test to measure improvements in time efficiency and a questionnaire based on the ISO/IEC 25010 standard to assess system benefits from user perception. The research findings indicate that the developed system significantly improved process efficiency, evidenced by a reduction in the average donation management time from 391.93 seconds to 29.79 seconds. Furthermore, the benefit evaluation from 30 respondents showed a very high level of user acceptance, with average scores for Functional Suitability (96.7%), Performance Efficiency (87.8%), Usability (85.6%), and Security (90%). Thus, this information system proves to be an effective solution to overcome the problems of manual donation management, successfully increasing efficiency, transparency, and donor trust.